Customer choice patterns in passenger rail competition - Paha, Johannes; Rompf, Dirk; Warnecke, Christiane (Transportation Research Part A-Policy and Practice, 2013)
This study explores determinants of customer choice behaviour in passenger rail competition on two cross-border routes, Cologne-Brussels and Cologne-Amsterdam. It fills a gap in the literature on competition in commercial passenger rail by relying on newly collected stated preference data from about 700 on-train interviews. Our multinomial Logit estimations reveal two important effects that are closely connected to (psychological) switching costs. First, the customers on the route Cologne-Amsterdam, for whom competition is a purely hypothetical situation, value a competitive market structure lower than customers on the already competitive route Cologne-Brussels. Second, travellers show a status quo bias with a preference for the service provider on whose trains they were interviewed. This effect goes beyond the impact exercised by explanatory variables capturing the observable differences of the services and customers, including loyalty-enhancing effects like the possession of customer cards. Our results imply that entry into the commercial passenger rail market may be more difficult than often thought. Thus, the study contributes to explaining the low level of competition in these markets in Europe. © 2013 Elsevier Ltd.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Competition; Discrete choice; Multinomial Logit; Passenger; Rail; Transport